The Natural History of Birds : From the French of the Count de Buffon; Illustrated with Engravings, and a Preface, Notes, and Additions, by the Translator. Volume 6 - Buffon, Georges Louis Leclerc, Comte de; Smellie, William (Place of publication not identified : publisher not identified, 1793)
Georges-Louis Leclerc, Comte de Buffon (1707-88), was a French mathematician who was considered one of the leading naturalists of the Enlightenment. An acquaintance of Voltaire and other intellectuals, he worked as Keeper at the Jardin du Roi from 1739, and this inspired him to research and publish a vast encyclopaedia and survey of natural history, the ground-breaking Histoire Naturelle, which he published in forty-four volumes between 1749 and 1804. These volumes, first published between 1770 and 1783 and translated into English in 1793, contain Buffon's survey and descriptions of birds from the Histoire Naturelle. Based on recorded observations of birds both in France and in other countries, these volumes provide detailed descriptions of various bird species, their habitats and behaviours and were the first publications to present a comprehensive account of eighteenth-century ornithology. Volume 6 covers parrots, parakeets and other foreign birds.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).